"The Semantics of Migration". Translation as Transduction: Remaking Meanings Across Modes - Sindoni, Maria Grazia (HERMES - Journal of Language and Communication in Business, 2016)
This paper adopts a multimodal critical discourse analysis (MCDA) approach to analyse how meanings are produced and circulated in British major corporate digital media outlets via the multimodal notion of transduction (Kress 1997; Mavers 2011; Newfi eld 2014). Transduction is a form of translation from one semiotic system to another one, for example from verbal language to images and vice versa. However, transductions cannot be interpreted as mere transferrals from one resource to another one, and are here interpreted as multiplying meanings (Lemke 2002). As a case study, this paper will select some online columns from the Telegraph and the Guardian, drawing from a monitor corpus that is under construction to date and that includes multimodal data from the British digital press reporting on the “European migrant crisis” in 2015. The columns selected for this study deal with how people on the move are and/or should be labelled (e.g. Migrants? Refugees? Asylum seekers? Potential terrorists? See Gabrielatos, Baker 2008; Baker et al. 2008). The columns will be commented qualitatively from a multimodal critical discourse framework of analysis, with the goal of shedding light on how pictorial materials (e.g. pictures and diagrams) can amplify, reduce or even contradict what is argued in the verbal text. In the conclusive remarks, some refl ections will be presented with a view to possible future lines of research.